ECONOMETRICS ANALYSIS FOR SUPPLY RESPONS OF WHEAT CROP USING AUTOREGRESSIVE DISTIRBUTED LAG MODELS( ARDL) FOR THE PERIOD (1970-2014) - & Al Hani, Al Baldawi (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2017)
The wheat crop is a strategic crop associated with food security. In order to increase the quantity of wheat production to meet the needs of the country, it is necessary to know how to increase the productivity of the unit of area of the crop to reduce the importations. Wheat is implanted in Iraq in large areas, especially in the northern governorates. The quantity of production and productivity for that crop is still limited, Compared to other countries in the neighboring countries and other countries of the world, and often fill the deficit through the import since wheat is implanted in most of the world countries , the average productivity of the wheat crop in Iraq for the period (1970 - 2014) amounted to (258.3) kg / dunums, Which shows the abuse of cultivated areas  The study were based on estimating the response function of wheat yield in Iraq using the ARDL for the evaluation of joint integration and the estimation of the short and long term equilibrium relationship. The main factors of the response to the produce of the area cultivated with wheat yield was organized as the area planted with wheat in Iraq for the previous year (dunums), the price of the wheat crop (JD / ton), the barley price (JD / ton) and the water discharge of the tigirs and Euphrats rivers , Production risk, price risk and rain (mm) was done (The price of the wheat crop and the price of the competing crop, the barley, the price risk and the rain. Then Checking the stability of the time series of studied variables and the results showed a lack of stability of the variables (the price of wheat, the price of the rival barley crop, the price risk and rain). And that the presence of unstable variables mean the existence of a false decline so it was taking the first difference to her, and through the Wald-statistic test turned out to be there is a common integration between the studied variables, and its noted that all transactions in the short term was significantly high degree except rain variable was not significant, the error correction parameter value amounted to (-0.594), means that about 59% of short-term imbalance in the cultivated wheat crop area In the Previous period (t-1) can be corrected in the current period (t) toward a long-term relationship equilibrium